THE INFLUENCE OF WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AND ASSETS OF THE SIDENRENG RAPPANG REGENCY REGION - Dewi; Andi Sri Kumala; Mifta Farid Salam (Universitas Ichsan Sidenreng Rappang, 2024)
This study aims to determine the influence of Work Discipline on the Performance of Employees of the Regional Finance and Assets Agency of Sidenreng Rappang Regency. The research method used is a quantitative method. The population in this study is 88 Employees of the Regional Finance and Assets Agency of Sidenreng Rappang Regency. Data was collected through questionnaires. The sampling technique used is a nonprobility sampling technique, namely purposive sampling. The results of the analysis showed that there was a significant influence between Work Discipline on Employee Performance, with a calculated t-value (3.208) that was greater than the t-value of the table (2,015). So that the hypothesis that states the influence of Work Discipline on Employee Performance can be accepted. The value of the determination correlation coefficient (R2) is 0.190 which means that the Employee Performance variable can be explained by the Work Discipline variable of 19,0% while the remaining 81,0% is explained by other factors of the variable. Keywords: Work Discipline, Employee Performance.